1994
DOI: 10.1016/s0006-3495(94)80640-x
|View full text |Cite
|
Sign up to set email alerts
|

A liquid crystalline phase in spermidine-condensed DNA

Abstract: Over a large range of salt and spermidine concentrations, short DNA fragments precipitated by spermidine (a polyamine) sediment in a pellet from a dilute isotropic supernatant. We report here that the DNA-condensed phase consists of a cholesteric liquid crystal in equilibrium with a more concentrated phase. These results are discussed according to Flory's theory for the ordering of rigid polymers. The liquid crystal described here corresponds to an ordering in the presence of attractive interactions, in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 38 publications
8
73
0
Order By: Relevance
“…The polyamines spermine or spermidine are ubiquitous compounds that stabilize the DNA double helix in vivo, and which, consequently, were intensively studied as a valuable model system for studying DNA organization in biological structures (25,32). Lx used in this report were partly composed of spermine-containing lipids and DNA and could constitute another model.…”
Section: Resultsmentioning
confidence: 99%
“…The polyamines spermine or spermidine are ubiquitous compounds that stabilize the DNA double helix in vivo, and which, consequently, were intensively studied as a valuable model system for studying DNA organization in biological structures (25,32). Lx used in this report were partly composed of spermine-containing lipids and DNA and could constitute another model.…”
Section: Resultsmentioning
confidence: 99%
“…8. The length of the fragments obtained ranged from 130 to 600 base pairs with 50% of 146 (Ϯ7) base pairs.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these data, several types of crystalline and liquid crystalline structures have been suggested for these DNA aggregates (5, 7). We have recently undertaken a study of these DNA aggregates using short (about 150 base pairs long) DNA molecules (8). In the case of the trivalent cation spermidine, we have found that the aggregate is generally biphasic and contains a liquid crystalline phase.…”
Section: Multivalent Cations With a Charge Of 3ϩ Or Greater Induce Thmentioning
confidence: 99%
“…The enhanced alignment of the polymer chains in the nematic state is the basis for several material properties and processes such as high strength fibers 1 and flow induced crystallization. [2][3][4][5][6] Solutions of DNA form lyotropic liquid crystalline phases under several biologically relevant conditions including molecular crowding, 7 large molecular weight, 8 polycationic agents ͑synthetic 9 and natural 10 ͒, and supercoiling in plasmid DNA. 11 Thus the nematic state of main-chain liquid crystalline polymers is a subject of importance in both materials science and biology.…”
Section: Introductionmentioning
confidence: 99%